Multidrug-resistant Salmonella spp. in fecal samples of pigs with suspected salmonellosis in Antioquia, Colombia, 2019-2021 - Juana L. Vidal; Viviana Clavijo; Luis R. Castellanos; Jeyashree Kathiresan; Ajay M.V. Kumar; Kedar Mehta; Jenny J. Chaparro-Gutiérrez (Pan American Health Organization, 2023)
Objectives. To determine the proportion of Salmonella enterica in fecal samples of live pigs with suspected salmonellosis analyzed at the diagnostic unit of the University of Antioquia, Colombia between 2019 and 2021, and examine the serotypes and antimicrobial resistance patterns. Methods. This was a laboratory-based cross-sectional study of routine data on fecal samples received from pig farms in all nine subregions of Antioquia state, Colombia. Salmonella spp. detection at the university is done using enrichment, selective culture, and polymerase chain reaction. Serotypes were identified using the Kauffmann-White scheme and isolates were tested for antimicrobial susceptibility using broth microdilution. Results. Of 653 samples tested, 149 (23%) were positive for S. enterica. Nine serotypes were identified. The most common were Salmonella Typhimurium (56%) and its monophasic variant (35%). Resistance to ampicillin (70%) was most frequently observed, followed by ciprofloxacin (55%), and sulfamethoxazole-trimethoprim (52%). No isolates were resistant to amikacin and gentamicin. Multidrug resistance (resistance to ≥ 3 classes of antibiotics) was observed in 61 (44%) isolates. Multidrug resistance was highest in S. Typhimurium (57%) compared with the other serotypes. Serotype was associated with multidrug resistance (p = 0.01), but age of the pig and sub-region were not. Conclusions. The proportion of Salmonella spp. and the associated high levels of multidrug resistance are of concern and may indicate irrational use of antimicrobials and poor management practices in pig production systems in the region. Strengthened surveillance is needed to monitor and improve farm management practices and the use of antimicrobials in farms in Colombia.